A Psychological View about the Unemployment and the Work Relationship’s Worsening - Peres, Rodrigo Sanches (2003)
The globalized world has faced intense metamorphosis in the last decades. The globalization, as well as its subproducts – the increase of the unemployment levels and the work relationship’s worsening – has contributed to the unemployees marginalization. The present research purpose is to delineate a profile of the unemployees and the vacancies offered by the the market in Assis (SP) town and region, in a psychological perspective about the work and the unemployment. The data was collected in the town Job Agency files and it was quantitavity analised and interpreted based on the researchers theoretical reference about the modern economic conjuncture.